Perbandingan Pendapatan Usahatani Paprika dengan Rumah Kaca dan Tanpa Rumah Kaca di Desa Pancasari dan Desa Gobleg - SARASWATI, KOMANG AGUS PUTRA; SUSRUSA, KETUT BUDI; DARMAWAN, DWI PUTRA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
The Comparison of Paprika Farming Income in the Greenhouse and Open-Field in Pancasari and Gobleg Village Cost and income analysis is the first step in determining the following activities in the whole farming processes, including in paprika farming. In the past, paprika cultivation has been commonly carried out in open-field. Nowadays, farmers have begun cultivating paprika with hydroponic method in greenhouses. However, such cultivation method requires higher investment and operation costs than open-field farming. This research aims to find out the comparison of paprika farming revenue and the income of paprika farmers who work as operators in greenhouses and open-field farms. This study was conducted in Pancasari and Gobleg village, Buleleng regency. The site selection was done purposely. The selection of respondents was done by census, namely, 24 greenhouse paprika farmers and 4 open-field paprika farmers. The method of analysis used in this study is comparative analysis of farm income and Mann-Whitney test to compare paprika farming revenue and the income of paprika operator farmers in greenhouse and open-field farms. The study suggests greenhouse paprika farming revenue and the income of greenhouse paprika operator farmers in a period of 8 months are Rp. 77,826,081/10 acre/MT and Rp. 101,085,543/10acre/MT. Meanwhile, the open-field paprika farming revenue and the income of open-field paprika operator farmers within the same period are Rp. 23,893,892/10 acre/MT and Rp. 32,024,389/10 acre/MT. The results of the Mann-Whitney Test analysis of the average paprika farming revenue and the income of paprika operator farmers in greenhouse and open-field per 10 acre are statistically significantly different.